Periodical maintenance of forest roads with a mobile stone crusher - Erber, Gernot (Array, 2020)
Forest road networks are exposed to damage by traffic, climate, timber harvesting and vegetation. To maintain their functionality, they must be maintained regularly. Periodical maintenance is required when the forest road surface layer is deteriorated and eroded. Well-graded material is required for replacing the forest road surface and often has to be sourced from gravel storage areas, which is costly and requires a large number of truck trips. Therefore, converting non-graded aggregate available on site into well-graded aggregate with a mobile stone crusher is considered a viable alternative.The present study was carried out during a periodical maintenance treatment at the Bavarian State Forest Enterprise and the effect of employing a mobile stone crusher was evaluated with regard to (1) forest road load bearing capacity development during a one-year period post-treatment, (2) particle size distribution of the surface layer material before and after crushing, and (3) its cost compared to other alternatives. Samples were collected pre- and post-operation for particle size distribution analysis, load bearing capacity was measured repeatedly with a light falling weight deflectometer and compared to an untreated reference section and cost of the treatment was compared to two alternatives.The mobile stone crusher was capable of reducing the non-graded to well-graded/close-to-well-graded material and particle size distributions aligned well with the recommendations for lime-water bonded surfaces. Load bearing capacity exceeded the threshold of 40 MN m-2 (Evd, elastic modulus dynamic) for primary forest roads at all times. It increased significantly after the treatment and remained on a significantly higher level throughout the following year. Absolute and relative increases were higher than on the untreated reference section.